Silence or expression? Spiral of silence in social networks - Liang, Silvia Wan-Ju; Chung, Kuo-Cheng (International Journal of Innovative Research and Scientific Studies, 2024)
Social networking sites such as Facebook have become the leading social platforms. However, publicly expressing opinions on Facebook may mean that a person has problems with isolation and is observing his or her environment. People who perceive their opinions as belonging to the majority will publicly express them. On the contrary, people who perceive their opinions as belonging to the minority will remain silent, which will lead to a spiral of silence theory. The purpose of this study is to explore the phenomenon of silent spirals in social and psychological capital networks by using social network users in Taiwan as the research subject. Structural equation modeling is used to verify the causal relationship between the research hypotheses and variables. Results show that there are significant differences in the mediation effect. Finally, this study presents conclusions and research directions.